2020
DOI: 10.1371/journal.pone.0239595
|View full text |Cite
|
Sign up to set email alerts
|

ICOS agonism by JTX-2011 (vopratelimab) requires initial T cell priming and Fc cross-linking for optimal T cell activation and anti-tumor immunity in preclinical models

Abstract: Immunotherapy checkpoint inhibitors, such as antibodies targeting PD-1 and CTLA-4, have demonstrated the potential of harnessing the immune system to treat cancer. However, despite encouraging results particularly with respect to survival, only a minority of patients benefit from these therapies. In clinical studies aimed at understanding changes in the immune system following immunotherapy treatment, ICOS (Inducible T cell CO-Stimulator) was shown to be significantly up-regulated on CD4+ T cells and this was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…5 aiii) as has previously been described 39 , 40 . By contrast, ICOS antibody treatment decreased T regulatory cells in the tumor when used as a single agent and also in combination with RT (ICOS Ab vs. Isotype p < 0.01; RT + ICOS Ab vs. RT p < 0.01), in line with the reported Treg depletion activity of this antibody in preclinical studies 35 . The non-Treg population of CD4 + T cells (CD4 + FoxP3 − ) were not significantly changed in proportion following treatment, and CD8 + T cell infiltrates were increased with RT and by ICOS antibody treatment (RT vs. Isotype p < 0.05; ICOS Ab vs. Isotype p < 0.05; RT + ICOS Ab vs. RT p = 0.0632) (Fig.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…5 aiii) as has previously been described 39 , 40 . By contrast, ICOS antibody treatment decreased T regulatory cells in the tumor when used as a single agent and also in combination with RT (ICOS Ab vs. Isotype p < 0.01; RT + ICOS Ab vs. RT p < 0.01), in line with the reported Treg depletion activity of this antibody in preclinical studies 35 . The non-Treg population of CD4 + T cells (CD4 + FoxP3 − ) were not significantly changed in proportion following treatment, and CD8 + T cell infiltrates were increased with RT and by ICOS antibody treatment (RT vs. Isotype p < 0.05; ICOS Ab vs. Isotype p < 0.05; RT + ICOS Ab vs. RT p = 0.0632) (Fig.…”
Section: Resultssupporting
confidence: 73%
“…However, given the observation that ICOS is a potential costimulatory molecule that is upregulated on T cells following radiation therapy (Fig. 1 ), we tested the effect of combining radiation with a novel ICOS agonist antibody 35 . We have previously demonstrated that for optimal tumor control, co-stimulatory antibodies such as OX40 antibody require different timing when compared to blocking antibodies such as anti-CTLA4 relative to the delivery of radiation therapy 36 .…”
Section: Resultsmentioning
confidence: 99%
“…Inducible endothelial ICOSLG expression has been described, particularly after inflammatory stimulation ( Khayyamian et al 2002 ; Klingenberg et al 2005 ), and regulates CD4 + ( Khayyamian et al 2002 ) and CD8 + T-lymphocyte functionality during cardiac allograft rejection ( Klingenberg et al 2005 ), suggesting that inflammatory-induced endothelial ICOSLG expression could activate and shape the local immune reaction at the site of injury or infection. In antitumoral immunity, Icos–Icosl signaling underpins successful antitumoral immune responses after blockade of the inhibitory ligand Ctla4 ( Fu et al 2011 ) or PD-1 ( Hanson et al 2020 ), providing rationale for the development of clinical ICOS-agonistic antibodies as second-generation immune oncology agents. These stimulating antibodies seem to avoid the superagonistic activity of earlier CD28 targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Agonists targeting co-stimulatory pathways could enhance T cell activity and revolve antitumor immune response [169]. A series of preclinical studies showed that co-stimulatory molecule agonists improved α-PD-1/PD-L1 efficacy [170][171][172][173][174][175][176]. At present, multiple clinical studies of co-stimulatory molecule agonists plus α-PD-1/PD-L1 are ongoing.…”
Section: Co-stimulatory Molecule Agonist Plus α-Pd-1/pd-l1mentioning
confidence: 99%